Steroid acne - Garofalo, L.; Carnimeo, L. (European Journal of Pediatric Dermatology, 2012)
A 27-year-old man was first observed for the presence of small pustules of the trunk. The family history of the patient put in evidence allergic asthma-rhinitis in the mother and atopic dermatitis in a brother. The patient himself was affected by atopic dermatitis in the first years and did not report acne. From about one year atopic dermatitis had recurred mainly affecting the hands and feet. Due to a severe deterioration of the dermatitis the patient had taken prednisone 1mg/kg per day for one month. From 7 days he presented the eruption responsible for the examination. On physical examination, beyond dyshidrosis-like atopic dermatitis of the hands and feet, there were asymptomatic monomorphic follicular pustules (Fig. 1, 2 and inset) on the upper third of the chest and the lower two thirds of the back in the absence of comedones. The history and the clinical findings led to the final diagnosis of steroid acne.